DEVELOPING THE CONFLICTOLOGOCAL COMPETENCE AMONG STUDENTS OF PROFESSIONAL AND TECHNICAL SCHOOL - Bondar, Valeriia; Kharkivska, Tetiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Conflict is an inevitable part of any interpersonal relations. Low conflictological competence among students, large amounts of anxiety and stress, significantly affect relations between peers, especially during the martial law in Ukraine. This is particularly relevant for the professional and technical schools. Inability to resolve conflicts peacefully is one of the key reasons of the increased number of conflicts among students, which leads to more cases of violence and bullying in the educational environment. Promoting tolerance, respect, support, decency, etc. is essential for teaching young people the crucial strategy for harmonious communication and coexistence in society. The objective of the article is to define conflictological competence and analyse, how students of professional and technical schools imagine the conflicts prevalence and management in the educational institution. The authors present the results of the survey conducted among 200 students from four professional and technical schools in Khmelnytska oblast and the city of Khmelnytsky in 2023. The survey has demonstrated the challenges related to the low conflict competence of the students and their inability to manage conflicts without using violence. Based on the survey results, the authors focus on the need for the implementation of the safe educational environments program aimed at combating bullying and violence through the restorative practices, and developing conflictological competence of students of professional and technical schools.